2012
DOI: 10.2140/jomms.2012.7.753
|View full text |Cite
|
Sign up to set email alerts
|

A pull-out model for perfectly bonded carbon nanotube in polymer composites

Abstract: A pull-out model for carbon nanotube (CNT) reinforced composite is presented to obtain the interface characteristic in which perfect bonding at the interface is considered. In the model, a partially embedded CNT in a cylindrical polymer matrix is subjected to an axial load at the open end. By using representative volume element (RVE) concept, analytical solutions are derived for axial and interfacial shear stresses in the CNT. Parametric studies are also conducted to obtain the influence of aspect ratio, modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A good number of research studies recommended that the strength and stiffness of CNT reinforced nanocomposites largely depends on the CNT/matrix interface and chemical bonding or non-bonding at the interface play a major role on the mechanical properties of nanocomposites [7,8,17,40,41,42,43,44,45,46]. Msekh et.…”
Section: Introductionmentioning
confidence: 99%
“…A good number of research studies recommended that the strength and stiffness of CNT reinforced nanocomposites largely depends on the CNT/matrix interface and chemical bonding or non-bonding at the interface play a major role on the mechanical properties of nanocomposites [7,8,17,40,41,42,43,44,45,46]. Msekh et.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental and numerical studies revealed that the axial Young's modulus of CNTs is in the terapascal range [Treacy et al 1996;Natsuki et al 2004;Shen and Li 2004;Liu et al 2005;Li and Guo 2008]. The quest for utilizing these exceptional mechanical properties of CNTs and their high aspect ratio led to the emergence of a new area of research on the development of CNT-reinforced nanocomposites [Odegard et al 2003;Ashrafi and Hubert 2006;Seidel and Lagoudas 2006;Esteva and Spanos 2009;Ray and Batra 2009;Meguid et al 2010;Khondaker and Keng 2012].…”
Section: Introductionmentioning
confidence: 99%